Faktor-Faktor Demografi Dan Efikasi Keuangan Yang Mempengaruhi Pilihan Keputusan Investasi (Survei Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Di Kota Tasikmalaya) - Ruchyat, Winona Susilawati; Rita Tri Yusnita; Kusuma Agdhi Rahwana (CV. ITTC INDONESIA, 2024)
This research aims to find out how demographic factors and financial efficacy can influence investment decision choices (Survey of Economics and Business Faculty Students in Tasikmalaya City). The method used is a quantitative method through a survey approach. With a sample of 102 students in Tasikmalaya City. The data used is primary data. The data obtained was then processed using validity tests, reliability tests, classical assumption tests, and statistical analysis tests. The research results show that demographic factors and financial efficacy can simultaneously significantly influence the investment decision choices of students at the Faculty of Economics and Business. Demographic factors can partially influence the investment decision choices of students in the City of Tasikmalaya significantly, and financial efficacy can partially influence the investment decision choices of Economics and Business Students in the City of Tasikmalaya significantly.